Absolute radiation tolerance of amorphous alumina coatings at room temperature. Issue 24 (15th December 2021) - Zaborowska, A.; Kurpaska, Ł.; Clozel, M.; Olivier, E.J.; O'Connell, J.H.; Vanazzi, M.; Di Fonzo, F.; Azarov, A.; Jóźwik, I.; Frelek-Kozak, M.; Diduszko, R.; Neethling, J.H.; et al.
Abstract: In this study structural and mechanical properties of a 1 μm thick Al2 O3 coating, deposited on 316L stainless steel by Pulsed Laser Deposition (PLD), subjected to high energy ion irradiation were assessed. Mechanical properties of pristine and ion-modified specimens were investigated using the nanoindentation technique. A comprehensive characterization combining Transmission Electron Microscopy and Grazing-Incidence X-ray Diffraction provided deep insight into the structure of the tested material at the nano- and micro-scale. Variation in the local atomic ordering of the irradiated zone at different doses was investigated using a reduced distribution function analysis obtained from electron diffraction data. Findings from nanoindentation measurements revealed a slight reduction in hardness of all irradiated layers. At the same time TEM examination indicated that the irradiated layer remained amorphous over the whole dpa range. No evidence of crystallization, void formation or element segregation was observed up to the highest implanted dose. Reported mechanical and structural findings were critically compared with each other pointing to the conclusion that under given irradiation conditions, over the whole range of doses used, alumina coatings exhibit excellent radiation resistance. Obtained data strongly suggest that investigated material may be considered as a promising candidate for next-generation nuclear reactors, especially LFR-type, where high corrosion protection is one of the highest prerogatives to be met.